Cityscape in the Era of Information and Communication Technologies - Bonenberg, Agata (The Urban Book Series,, 2018)
This book discusses the impact of information and communication technologies, particularly social media, on the structure and landscape of contemporary cities. It presents a multidisciplinary range of theories and practical case studies and addresses a broad readership, from graduate students to practitioners active in the fields of urbanism and the architectural design of urban space. The book includes a wealth of illustrations depicting contemporary architecture and exemplary modern public spaces, as well as diagrams and tables that optimally visualize the concepts and ideas discussed.